O enfermeiro como facilitador de processos de educação permanente em saúde: fronteiras e perspectivas da atuação profissional - Pinto, Mary Cristina Ribeiro Lacôrte Ramos (Universidade Federal de São Carlos, 2011)
The object of the research was the inclusion of nurses in the educational processes that occur in the Family Health Strategy (ESF), adopted at the reorganization of the Primary Health Care in Brazi. The Permanent Education in Health (EPS) is presented as a management tool, providing analysis and reconfiguration of work processes in mind the principles of the Unified Health System (SUS). There are different references ordering the educational practices of nurses responsible for conducting formal educational measures regarding nursing teams and community health agents (ACS). The objective was to examine how nurses are included in the educational processes that occur in the ESF, to identify their perception on the EPS and the tools used in their educational practice, and analyzing domestic production on the educational processes developed with teams of nurses, the the grounds of EPS. An review of literature and qualitative research approach was conducted and semistructured interviews with nine nurses who work in the ESF in five municipalities of São Paulo State was also conducted. The interpreted the data from thematic categorical analysis, resulted in: Family Health means prevention, the centrality of the nurse coordinating the work with the family health: strengthening the division in the work and education process, Education tutoring and / or Chief without educating and the EPS and the family on health: real or virtual? The results showed that review of educational activities are not consistent with the EPS, which educational processes are characterized by thematic technical contemplating the needs of workers, however, also point to the absence of answers to everyday problems. The interview results showed that the nurses to attend to family health means conducting educational activities in preventive logic / programming, emphasizing the importance of home visits and SUS. The nurses remain linked to the coordination and organization of work, ignoring the self-sufficiency and self-management of each professional and strengthening technical and social division on the team. They also carry out educational activities with employees, but do not conceive to be their assignment and do not consider themselves able to do so. The educational actions are reproduced as the transmission of knowledge and privilege the SUS instead of the nursering, responsible for the curative dimensions of care. Nurses don't know the concept of EPS and use its own tools of traditional banking education, though occasionally also employ so inadequate inherent in the EPS tools. It is concluded that the PEH did not acquire concreteness to the nurses and daily life of ESF in the setting of research, although there are nuances of attitudes and judgments consistent with it. It is considered the relevance of investment to ensure the continuity of the embryonic and evolutionary accomplishment of the EPS in the ESF and SUS.
Keywords: Enfermagem; Educação do trabalhador; Política de saúde; Sistema Único de Saúde (Brasil); Saúde coletiva; Permanent education in health; Family health strategy; Nurse; CIENCIAS DA SAUDE::ENFERMAGEM